Zaposlovanje starejših v Sloveniji - Žakelj, Tjaša (Socialno delo, 2019)
Economic growth and a growing demand for the labour force are reflected in a reduced number of unemployed and a declining unemployment rate. However, the increasing possibilities for employment are not equally distributed across demographic groups. Employers' pragmatism and the deep-set stereotypes about age, are effecting the preference for younger candidates. Despite this, the prolonging working lives and the increasing percentage of the older workforce are introducing new challenges for the employers in sense of providing appropriate placement of the aging workforce in the work processes, adapting to their abilities and making use of the potentials in employment of older workers. The articles points to the challenges of recruiting the older jobseekers in time of prolonging working lives and increasing labour demand, based on the indicators of employment and unemployment, structural characteristics of older unemployed, and identification of the factors influencing the active aging of the workforce.
Keywords: brezposelnost; delovna sila; staranje; starejši ljudje; trg dela; zaposlenost